Trade Preference Erosion : Measurement and Policy Response - Hoekman, Bernard; Martin, Will; Primo Braga, Carlos A. (Washington, DC: World Bank and Palgrave Macmillan, 2012)
The multilateral trade system rests on the principle of nondiscrimination. The most-favored-nation (MFN) clause embodied in article one of the General Agreement on Tariffs and Trade (GATT) was the defining principle for a system that emerged in the post, Second World War era, largely in reaction to the folly of protectionism and managed trade that contributed to the global economic depression of the 1930s. From its origins, however, the GATT has allowed for exemptions from the MFN rule in the case of reciprocal preferential trade agreements. It also permits granting unilateral (nonreciprocal) preferences to developing countries. To provide some background for the debate on the potential extent and implications of preference erosion, the chapters in this volume review the value of preferences for beneficiary countries, assess the implications of preference erosion under different global liberalization scenarios, and discuss potential policy responses. One set of chapters focuses on the nonreciprocal preference schemes of individual industrial countries, particularly, Australia, Canada, Japan, the United States, and the member states of the European Union (EU). A second set of chapters considers sectoral features of these preference schemes, such as those applying to agricultural and nonagricultural products, and the important arrangements for textiles and clothing. A final set of chapters considers the overall effects of preferences and the options for dealing with preference erosion resulting from nondiscriminatory trade liberalization.